Language Teaching and Dictionary Use: An Overview - Carstens, Adelia (Lexikos, 1995)
The main objective of language teaching is to improve language proficiency with regard to reading, writing, speaking and listening. The dictionary is one of the aids that can be used to attain this goal. There are however a number of stumbling blocks in the way of optimal utilization of dictionaries. Poor reference skills and a lack of knowledge with regard to dictionary typology seem to be the most prominent among these. It is argued that reference skills could be developed by the teaching of reference strategies, preferably by integrating dictionary-using exercises with other language learning activities, and by structuring these exercises according to the stages of the actual reference process. Dictionary pedagogy should ideally be introduced in the L1 class during primary education, but students will definitely still benefit if dictionary skills are taught during the intermediary stages of second or foreign language learning. It is anticipated that students who have become convinced of the problem-solving potential dictionaries through personal experience will become independent learners who will continue using dictionaries even after the years of formal education.